2021
DOI: 10.7759/cureus.20406
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Medical Education Delivery Preferences Among Physicians and Advanced Practice Providers in Emergency Medicine

Abstract: Study objectiveWe investigate the continuing medical education delivery preferences among emergency medicine providers, both physicians and advanced practice providers (APPs), within a large, national emergency medicine group. MethodsA survey was sent via email to all emergency medicine health care providers in the practice group, including questions evaluating both delivery method and topic preference for continuing education. The study was sent to providers whom the group employed from October 2019 through J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These preferences are consistent with previous studies that online learning is important. A study of emergency medicine physicians in the US showed that 65.62% of respondents would like to study via video, 13.98% via classroom (instructor-led training), and 5.68% via live webinars [ 27 ]. Additionally, a convergence mixed method study in Rwanda showed that participants preferred blended learning the most (online and face-to-face learning combined) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These preferences are consistent with previous studies that online learning is important. A study of emergency medicine physicians in the US showed that 65.62% of respondents would like to study via video, 13.98% via classroom (instructor-led training), and 5.68% via live webinars [ 27 ]. Additionally, a convergence mixed method study in Rwanda showed that participants preferred blended learning the most (online and face-to-face learning combined) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a convenient, accessible, and cost-effective way to promote positive change and improvement in patient behavior in health promotion research [24][25][26]. This strategy also accords with the preference of general practitioners for short online on-demand options, including videos, podcasts, and written material [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Also, when used by learners from other specialties, podcasts shape their medical knowledge and alter their clinical practice [ 13 ]. It has also been shown that medical professionals prefer podcasts to other forms of media in education delivery, specifically, podcasts over video recordings, printed media, and in-person education [ 14 , 15 ]. These factors should be taken into consideration when evaluating our findings.…”
Section: Discussionmentioning
confidence: 99%